Pengembangan Proses pada Sistem Anaerobic Baffled Reactor untuk Memenuhi Bakumutu Air Limbah Domestik - Elis Hastuti; Reni Nuraeni; Sri Darwati (Direktorat Bina Teknik Permukiman dan Perumahan, 2017)
The wastewater treatment infrastructure had provided by the government mainly through application of communal wastewater treatment plant (WWTP). The treatment process of communal WWTP applied generally anaerobic system, such as Anaerobic Baffled Reactor (ABR) technology, but most of treated water do not meet effluent standard. This paper aims to research the characteristics of the organic removal and treatment upgrading process in the communal ABR system, including process modification or combination with other system. Research carried out in several communal WWTP has applied since the year 2012-2013 in Cimahi City, West Java. Method of evaluation was conducted in the WWTP management through observation of serviced community, operation and maintenance, water quality test both physically and chemicaly. Method of qualitative descriptive for analysis factors affecting the process performance of ABR and potential process upgrading of ABR system according to characteristic of ABR system. The organic removal in ABR system is influenced by the management, existence of pra treatment unit, acclimatization process, water consumption and environment of serviced area. Upgrading process of ABR system can be performed by modification of baffle design, start-up process, maintenance biomass, hybrid system, recirculation systems and application of further treatment. The review these alternative of ABR upgrading process are important in the ABR planning standard to achieve treated water meet effluent standard.